PELATIHAN KARAWITAN BAGI MAHASISWA PGSD FKIP UNS UNTUK MEDIA PEMBELAJARAN PENDIDIKAN KARAKTER - Danis Sugiyanto (Abdi Seni, 2020)
PGSD UNS is one of the faculty and graduate study programs or instituted educators especially for the elementary school level (SD). In formal learning, the music has been entered as a local content subject area of art. Musicians as a means of character education are expected to contribute equipment to the prospective educators. Full of musical rules, complexity, and subtlety can infuse character education, especially for students of PGSD UNS. Some of the materials studied in this musical training are very relevant in order to equip students who will jump in the world of education and society.Key words: Karawitan, character education